IMPLEMENTASI BUKU SUKU KATA UNTUK MENDUKUNG KETERAMPILAN BERBICARA SISWA KELAS II SDN TAMBAKAJI 05 - Inggar Rezha Listiary; Firdha Rosdiana; Tri Hariyanti; Moh. Farizqo Irvan (LPPM Universitas Cipta Mandiri, 2025)
Speaking skills are an essential component of Indonesian language learning, supporting students' critical thinking, reasoning abilities, and self-confidence (Dwi Padmawati et al., 2019). This study employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation (Kurniasari, 2022). The research subjects consisted of a second-grade teacher and four students. The findings revealed that the main obstacles in speaking skills include psychological factors (such as shyness and fear of making mistakes), linguistic limitations (limited vocabulary), and teaching approaches that do not adequately support active student participation (Susanti, 2022). The identified strategies include the use of interactive methods such as storytelling, small group discussions, and role-playing, along with the creation of a safe and supportive learning environment. The choice of this topic is based on the importance of speaking skills in supporting students' communication and learning success, as well as the lack of focus on this aspect at the elementary school level